Infraspinatus atrophy due to Bennett lesion causing suprascapular nerve palsy - Bautista Juan Miranda; Fernández-Jara Javier; Bautista Santiago Miranda; Fernández-Miranda Pablo Menéndez; Mora María Valencia; San José Begoña Gutiérrez; Estévez Mateo González; Molina Blanca Mur; Vázquez Patricia Patilla (Journal of Ultrasonography, 2021)
We report the case of a 19-year-old professional volleyball player who presented with right shoulder pain exacerbated during sports activity. On physical examination, infraspinatus atrophy was evident. As the clinical setting suggested suprascapular nerve entrapment syndrome, shoulder MR and later CT were performed. The results showed radiological signs of subacute-chronic infraspinatus muscle denervation and a Bennett lesion of the shoulder, presumably due to chronic repetitive trauma during the classical overhead swing in volleyball. The patient agreed to surgical treatment, and arthroscopic decompression was achieved. After months of rehabilitation, the pain gradually subsided, the infraspinatus muscle recovered its trophism, and the patient progressively returned to her regular sports activity.